Smashing, Shaming, or Polite Fun and Joy? How Workplace Humor Influences Positive Well-Being in South Korean Workplaces - Kim, Hee Sun; Plester, Barbara (Frontiers in Psychology, 2021)
Humor is contextual, ambiguous, and varies within cultures but is widely associated with positive outcomes such as well-being and happiness. While humor is universal and enhances interpersonal relationships, which can benefit psychological well-being, we argue that humor can also diminish psychological well-being in Confucian-based, South Korean workplaces. Our research questions asks: how do hierarchical workplace relationships influence shared humor and positive well-being in Korean workplace contexts? Our contextual, ethnographic research includes in-depth field observations and semi structured interviews in three Korean organizations. Traditional Confucian-based cultures value face-saving, trust, and harmony while emphasizing formality and hierarchy. Korean honorifics maintain harmony, hierarchy and politeness which creates benefits for group processes and influences the sharing of humor. Humor is enacted in accordance with workers’ hierarchical status which has a significant impact upon the types of humor shared and the responses available to subordinate employees. Investigating these dimensions in Korean workplaces we argue that honorifics and hierarchy influence humor interactions in complex ways that have implications for psychological well-being.